Integrasi IQ, EQ, Penguasaan Teknologi dan Ketelitian pada Kualitas Keputusan Organisasi - Ruslaini Ruslaini; Ekawahyu Kasih (Journal Of Business, Finance, and Economics (JBFE), 2024)
In the current era of rapid technological disruption, effective decision-making within organizations is crucial for maintaining competitive advantage and operational sustainability.This study investigates the elements that lead to prudent decision-making, emphasizing the combination of emotional and intellectual intelligence (EQ), constant advancement in technological and information mastery, and meticulousness. The study identifies how these elements interact to improve decision quality by synthesizing the body of previous information. The results show that IQ and EQ together account for 50% of decision quality, whereas knowledge, technological proficiency, and meticulousness account for 20% and 30% of the total, respectively. While EQ focuses on understanding and controlling emotions, IQ covers cognitive skills like logical reasoning and problem-solving. Technology and knowledge mastery facilitate decision-making by delivering pertinent information in a timely manner via efficient knowledge management systems (KMS). Meticulousness, characterized by careful attention to detail, is essential for thorough and precise decision-making. The integration of intellectual intelligence (IQ) and emotional intelligence (EQ), technological proficiency, and meticulousness forms a comprehensive framework for achieving wise and accurate decisions, ensuring that organizations remain agile and responsive to dynamic environments.